C-Reactive Protein: An In-Depth Look into Structure, Function, and Regulation. (15th December 2014) - Salazar, Juan; Martínez, María Sofía; Chávez-Castillo, Mervin; Núñez, Victoria; Añez, Roberto; Torres, Yaquelin; Toledo, Alexandra; Chacín, Maricarmen; Silva, Carlos; Pacheco, Enrique; Rojas, Joselyn; Bermúdez, Valmore
Abstract : Cardiovascular disease is the leading cause of morbidity and mortality in the adult population worldwide, with atherosclerosis being its key pathophysiologic component. Atherosclerosis possesses a fundamental chronic inflammatory aspect, and the involvement of numerous inflammatory molecules has been studied in this scenario, particularly C-reactive protein (CRP). CRP is a plasma protein with strong phylogenetic conservation and high resistance to proteolysis, predominantly synthesized in the liver in response to proinflammatory cytokines, especially IL-6, IL-1 β, and TNF. CRP may intervene in atherosclerosis by directly activating the complement system and inducing apoptosis, vascular cell activation, monocyte recruitment, lipid accumulation, and thrombosis, among other actions. Moreover, CRP can dissociate in peripheral tissue—including atheromatous plaques—from its native pentameric form into a monomeric form, which may also be synthesized de novo in extrahepatic sites. Each form exhibits distinct affinities for ligands and receptors, and exerts different effects in the progression of atherosclerosis. In view of epidemiologic evidence associating high CRP levels with cardiovascular risk—reflecting the biologic impact it bears on atherosclerosis—measurement of serum levels of high-sensitivity CRP has been proposed as a tool for assessment of cardiovascular risk.